Potential Noise Intensity from Heavy Equipment during the Construction Phase of the Campus in Surabaya: Potensi Intensitas Kebisingan Dari Alat Berat pada Tahap Konstruksi Kampus di Kota Surabaya - Afif Rasendriya Haryu; Galang Eigy Hermawan; Tuhu Agung Rachmanto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Educational facilities are one of the public service facilities in developing and improving the quality of human resources. Over time, educational facilities continue to experience improvements, one of which is the campus. Campus improvements are inseparable from the development process that will have an impact on the surrounding environment. One of the impacts is noise. Noise if not handled properly will disrupt activities and public health. This study aims to identify the heavy equipment used in the construction phase of the XYZ campus, estimate the noise levels generated and received by receptors and plan appropriate impact management for the local community. The study method is a qualitative descriptive analysis with the data used in the form of primary and secondary data. Data analysis is in the form of mathematical calculations and comparisons with noise quality standards. The heavy equipment used are trucks, excavators, dozers, and cranes. The results of the estimated noise level received by receptors in the mobilization-demobilization activities of heavy equipment & materials are 73.25 dB(A), land preparation is 73.85 dB(A), and building construction work is 75.85 dB(A). According to the Minister of State for the Environment Decree No. 48 of 1996, the noise intensity of the three construction activities slightly exceeds the residential quality standards. Management or mitigation measures have been planned, including limiting operating hours, installing fences at least 2 meters high, and regular heavy equipment maintenance. After management, the estimated noise levels received by the receptors for each activity are 55.55–58.15.